Study of the physical mechanical properties of capirona wood (Calycophyllum spruceanum (bentham)Hooker f.ex.schumann) as potential for solid wood flooring production - Egoavil Cueva Galvez, Graciela Isabel (2023)
[The aim of this study was to determine the physical-mechanical properties of a 20-year-old plantation of the species Calycophyllum spruceanum, known as "capirona" in Peru, due to its potential in wood flooring production. Samples were taken from six trees in a plantation in Curimaná-Ucayali, Peru, and tests were conducted according to ASTM standards (ASTM D 143-94 – 2 000). The results revealed that capirona has a basic density of 0.68 g/cm3, categorizing it as heavy wood, with moderate dimensional stability. Mechanical properties indicated high resistance to bending and parallel compression, and very high resistance to perpendicular compression, hardness, shear, and toughness. According to NTP 251.135.2013, capirona wood was positively evaluated, highlighting its potential for the production of solid wood flooring].